Moral challenges of Ukrainian post-secular society: social and value worth of tolerance - Горохолінська, Ірина (My University, 2019)
У статті осмислено морально-етичну ситуацію в Україні крізь призму аналізу тих реалій, котрі характеризують соціальну та культурно-духовну реальність сьогодення. Констатуючи, що одним із найважливіших правкожної особи є її право на повагу до власної гідності, авторка підкреслює, що реалізація поваги до Іншого длясучасної України є проблемою, котра вимагає нагального розв'язання. Задля кристалізації ключових длядослідження аргументів у статті дається характеристика конкретних наявних в українському суспільстві сис-тем "вчинків" та "виборів", котрі надають змістовної наповненості поняттям "добра" і "зла" на шляху накрес-лення аксіологічних векторів задля корегування диспропорцій, що характеризують українські суспільні тадуховно-культурні реалії. Методологічною системою координат статті є елементи ідейного доробку Ф. Ніцше -задля типологізації дійсності, та етична система орієнтирів християнства - для увиразнення бажаних, продик-тованих провідною традицією, ідеалів. Авторка звертається й до вчення Ч. Тейлора - для віднаходженняетичних ідейних важелів, здатних гармонізувати взаємини з Іншим як усередині країни, так і за її межами.Шляхом позитивного перетворення реалій в Україні (в морально-духовному, і соціально-громадянському на-прямках), на думку авторки, є усвідомлене прагнення подолати стереотипи рабської моралі (коли всі для всіх "загроза") та узалежненої системи дій. Задля цього потрібно щиро й спільнотно працювати в руслі інтелекту-ального збагачення нації, духовного її розвитку - через систему освіти та культурні ініціативи. The moral and ethical situation in Ukraine is considered in an issue in the light of analysis ofthe realities which characterize the modern social, cultural and spiritual reality. Having concludedthat the main right of any person is a right to own dignity, an author highlights that the realizationof respect for Other is a problem for modern Ukraine which demands an urgent solution. Acharacteristic of presented in Ukrainian's society systems of "deeds" and "choices" is provided inthe issue for determination of the key research arguments. The systems give the essential meaningsto "good" and "evil" definitions on the way of highlighting some axiological vectors for imbalancecorrection that characterize Ukrainian social, cultural and spiritual realities. The methodologicalcoordinate system of an issue refers to the elements of Fr. Nietzsche's work which is used forreality peculiarities' definition, and to the ethical system of Christian guidelines which are notedfor ideas' expressiveness under current tradition. An author appeals to Ch. Taylor's studies for asearch of crucial ethical ideas, which are able to harmonize the relationships with Others withina country as well as beyond it. Due to the author a way of positive realities transformation (inmoral, spiritual, social and civil directions) in Ukraine consists in deliberate wish to overcome thestereotypes of slave morality (when everyone is a "threat" for everybody) and change the systemof actions depended on such type of morality. That required the true community work in a directionof national intellectual enrichment, national spiritual development according to the system ofeducational and cultural initiatives.
Моральні виклики постсекулярного українського соціуму: соціальна й ціннісна значущість толерантності
Keywords: tolerance; respect for other; ressentiment; “morality of a slave and aristocrat”; Christian ethics; post-secularity; толерантність; повага до іншого; постсекулярність; християнська етика; ресентимент